The Dark Side of Fibroblasts: Cancer-Associated Fibroblasts as Mediators of Immunosuppression in the Tumor Microenvironment - Monteran, Lea; Erez, Neta (Frontiers in Immunology, 2019)
Cancer-associated fibroblasts (CAFs) are prominent components of the microenvironment in most types of solid tumors, and were shown to facilitate cancer progression by supporting tumor cell growth, extracellular matrix remodeling, promoting angiogenesis, and by mediating tumor-promoting inflammation. In addition to an inflammatory microenvironment, tumors are characterized by immune evasion and an immunosuppressive milieu. In recent years, CAFs are emerging as central players in immune regulation that shapes the tumor microenvironment. CAFs contribute to immune escape of tumors via multiple mechanisms, including secretion of multiple cytokines and chemokines and reciprocal interactions that mediate the recruitment and functional differentiation of innate and adaptive immune cells. Moreover, CAFs directly abrogate the function of cytotoxic lymphocytes, thus inhibiting killing of tumor cells. In this review, we focus on recent advancements in our understanding of how CAFs drive the recruitment and functional fate of tumor-infiltrating immune cells towards an immunosuppressive microenvironment, and provide outlook on future therapeutic implications that may lead to integration of preclinical findings into the design of novel combination strategies, aimed at impairing the tumor-supportive function of CAFs.